The 1-minute sit-to-stand test in adults with cystic fibrosis: Correlations with cardiopulmonary exercise test, 6-minute walk test, and quadriceps strength - Gruet, M.; Peyré-Tartaruga, LA; Mely, L.; Vallier, J-M (Respiratory Care, 2016)
n/a
cited By 36